Evaluasi Program Pembelajaran Tilawah Qur’an Dengan Menggunakan Model CIPP Di MTs Swasta Cendekia Medan - Elysa, Elysa (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research aims to review the process and implementation of evaluating Al-Qur'an Recitations using the CIPP model. Through the Al-Qur'an recitation program, students can gain insight into knowledge of how to read, recite and write verses of the Al-Qur'an by knowing the rules that have been set, such as mahkorijul letters, short lengths, tajwid rules, and ghorib so that they do not there is a change in meaning. This research problem focuses on the evaluation of the CIPP System for the Al-Qur'an Recitation Program at Private MTs Cendikia. This research aims to find out: 1) the implementation of Al-Qur'an recitation program activities at the Private Scholar MTs. 2) evaluate the Al-Qur'an recitation program using the CIPP system at MTS Private Scholar. The type of research that will be carried out in this research is qualitative field research. The subject of this research is: Tahfiz teacher in applying recitations of the Qur'an at the Private Scholar MTs. The data collection techniques required are observation and documentation. As well as data analysis using data reduction, data display, and conclusion drawing/verification." The results showed that: 1) The implementation of Al-Qur'an recitation program activities at Private MTS Cendikia was carried out using two methods, namely the Iqra' and Al-Baghdadi methods 2) Evaluation of the Al-Qur'an recitation program using the CIPP system at Private MTs Cendikia, namely by using Context Evaluation (context), namely the teacher's module contains materials, tests and assignments. Al-Qur'an reading and writing learning and context evaluation are carried out to see how students understand and as material for reflection for teachers. In the Input Evaluation (input) the teacher evaluates input to students, thus the teacher assesses whether the program is effective or not. Third, Evaluation Process (process) of strategy implementation and use of facilities/material capital in real field activities. Next, Product Evaluation, focuses on measuring success.